THEORETICAL BASIS OF EPIDEMIC PROCESS - SERGEY L. Kolpakov (Фундаментальная и клиническая медицина, 2018)
Here I analyze current knowledge and prospects regarding the concept of epidemic process. Aim. To systematize our understanding on epidemic process, to perform the synopsis, and to denote the prospects in the field. Materials and Methods. To apply a critical analysis, I employed Frege’s semiotic triangle (sign - concept - denotation). Publications on epidemic process were utilized as the research material. Results. Epidemic process considers diseases at the population level that demands understanding principles of research object definition and determination of the research subject, representing a concept content. I structured the concept content, logical models of epidemic process, and mechanisms of its development. The new theory of epidemic process formation should be based on the social organization. To classify types of incidence, I annotate types of social relationships. In turn, development of epidemic process is defined by distinct incidence types.